Bioactive oleanane-type saponins from Hylomecon Japonica. (October 2021) - Li, Fei; Wu, Si-Tong; Qu, Ming-Hui; Wang, Yi-Xiao; Ma, Chun-Liu; Yu, Bai-Hong; Wang, Guang-Shu
Abstract: Six undescribed oleanane-type saponins, named as Hylomeconosides L-Q, were isolated from the whole herb of Hylomecon Japonica, their structures were determined by analysis of 1D and 2D-NMR ( 1 H– 1 H COSY, HSQC, and HMBC) spectroscopic data, mass spectrometry (HRESI-MS) and chromatographic data (GC and LC). Their structures were identified as 3- O -β-D-galactopyranosyl-(1 → 2)-β-D-glucuronopyranosyl gypsogenin 28- O -β-D-galactopyranosyl-(1 → 3)-α-L-rhamnopyranosyl-(1 → 2)-β-L-arabinopyranoside; 3- O -β-D-galactopyranosyl-(1 → 2)-β-D-glucuronopyranosyl gypsogenin 28- O -β-D-xylopyranosyl-(1 → 4)-α-L-rhamnopyranosyl-(1 → 2)-β-D-quinovopyranoside; 3- O -β-D-glucuronopyranosyl gypsogenin 28- O -β-D-xylopyranosyl-(1 → 3)-β-D-xylopyranosyl-(1 → 4)-α-L-rhamnopyranosyl-(1 → 2)-β-D-quinovopyranoside; 3- O -β-D-xylopyranosyl-(1 → 3)-β-D-glucuronopyranosyl gypsogenin 28- O -β-D-xylopyranosyl-(1 → 4)-α-L-rhamnopyranosyl-(1 → 2)-β-D-quinovopyranoside; 3- O -β-D-galactopyranosyl-(1 → 2)-[α-L-rhamnopyranosyl-(1 → 3)]-β-D-glucuronopyranosyl quillaic acid 28- O -β-D-xylopyranosyl-(1 → 3)-β-D-xylopyranosyl-(1 → 4)-α-L-rhamnopyranosyl-(1 → 2)-β-D-quinovopyranoside; 3- O -β-D-galactopyranosyl-(1 → 2)-[α-L-rhamnopyranosyl-(1 → 3)]-β-D-glucuronopyranosyl quillaic acid 28- O -β-D-xylopyranosyl-(1 → 3)-β-D-xylopyranosyl-(1 → 4)-α-L-rhamnopyranosyl-(1 → 2)-β-D-galactopyranoside. Hylomeconosides L-Q showed selective cytotoxicities against human cancer cell lines A549, AGS, HeLa, Huh 7, HT29 and K562. These results represent a contribution to the chemotaxonomy of the saponins of Hylomecon Japonica and their bioactivities. Graphical abstract: Image 1 Highlights: Six undescribed oleanane-type triterpenoid saponins, were isolated from Hylomecon japonica. Their structures were elucidated by 1D, 2D-NMR and HRESIMS analyses. The triterpene saponins showed selective cytotoxicities against human cancer cells A549, AGS, HeLa, Huh7, HT-29 and K562.